# Algebra - Equation

m/n = p - 6

Question omitted.

It may be solving for each variable.

### Comments for Algebra - Equation

 Oct 13, 2011 Solve Equation by: Staff Question: m / n = p - 6 Answer: You didn’t include a question with your equation, so I’m not sure what you need. You can solve for each variable as follows: 1. Solve for m m / n = p - 6 to remove the variable n from the left side of the equation, multiply each side of the equation by n n * (m / n) = n * (p - 6) m * (n / n) = n * (p - 6) m * (1) = n * (p - 6) m = n * (p - 6) applying the distributive law to n * (p - 6) m = n * p + n * (- 6) m = np + n * (- 6) m = np - 6n 2. Solve for n m / n = p - 6 to remove the variable n from the denominator of the fraction m / n, multiply each side of the equation by n n * (m / n) = n * (p - 6) m * (n / n) = n * (p - 6) m * (1) = n * (p - 6) m = n * (p - 6) to eliminate (p - 6) from the right side of the equation, divide both sides of the equation by (p - 6) m / (p - 6) = n * (p - 6) / (p - 6) m / (p - 6) = n * [(p - 6) / (p – 6)] m / (p - 6) = n * (1) m / (p - 6) = n n = m / (p - 6) 3. Solve for p m / n = p - 6 to remove the -6 from the right side of the equation, add 6 to each side of the equation (m / n) + 6 = p - 6 + 6 (m / n) + 6 = p + 0 (m / n) + 6 = p p = (m / n) + 6 Thanks for writing. Staff www.solving-math-problems.com